2019
DOI: 10.1038/s41598-019-42865-9
|View full text |Cite
|
Sign up to set email alerts
|

Differences in resource use lead to coexistence of seed-transmitted microbial populations

Abstract: Seeds are involved in the vertical transmission of microorganisms in plants and act as reservoirs for the plant microbiome. They could serve as carriers of pathogens, making the study of microbial interactions on seeds important in the emergence of plant diseases. We studied the influence of biological disturbances caused by seed transmission of two phytopathogenic agents, Alternaria brassicicola Abra43 (Abra43) and Xanthomonas campestris pv. campestris… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 74 publications
(95 reference statements)
0
25
0
1
Order By: Relevance
“…However, in their case, ANI values were clearly above the species delineation threshold of 94%, whereas dDDH values were below 70%. Nevertheless, our findings could indicate that SCA7 is a member of the species P. helmanticiensis or of a yet non-described Pseudomonas species, which could eventually include P. koreensis CFBP13504 identified in a metagenomics analysis from radish seeds (Torres-Cortés et al, 2019 ) and P. koreensis CI12 isolated from soybean rhizosphere (Lozano et al, 2017 ). Further phenotypic comparison to the different Pseudomonas type strains could support the correct assignment.…”
Section: Discussionmentioning
confidence: 88%
“…However, in their case, ANI values were clearly above the species delineation threshold of 94%, whereas dDDH values were below 70%. Nevertheless, our findings could indicate that SCA7 is a member of the species P. helmanticiensis or of a yet non-described Pseudomonas species, which could eventually include P. koreensis CFBP13504 identified in a metagenomics analysis from radish seeds (Torres-Cortés et al, 2019 ) and P. koreensis CI12 isolated from soybean rhizosphere (Lozano et al, 2017 ). Further phenotypic comparison to the different Pseudomonas type strains could support the correct assignment.…”
Section: Discussionmentioning
confidence: 88%
“…Beyond the scope of this study, the taxonomic identity and biological characteristics of the functional guilds (e.g., Bacillus spp., Pseudomonas spp.) could be accurately defined using culture-based approaches; following which, the potential roles of the isolates in pathogen transmission and suppression, disease resistance, and/or plant growth-promotion can be assessed using in vitro and in planta tests as described elsewhere (Mitter et al, 2017;Torres-Cortés et al, 2019;Zhang et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, seed transmission serves as one of the major dispersal mechanisms for plant pathogens, which could transiently colonize the seed (seed-borne) or be transmitted to the seedling (Darrasse et al, 2007). Torres-Cortés et al (2019) reported the transmission of two plant pathogens, a fungus Alternaria brassicicola and a bacterium Xanthomonas campestris, from the radish seeds to the plantlets. In the present study, we found that several potential rice pathogens, such as Pantoea spp.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Torres-Cortés et al ( 2019) looked at how transmission of several bacterial pathogens impacted the composition of Raphanus sativus seed microbiomes. They found that these pathogens did not alter the composition of the seed microbiome, suggesting that differences in resource usage (niche partitioning) lead to coexistence between taxa (Torres-Cortés et al, 2019). A more complete understanding of the types and outcomes of microbial species interactions prior to and during seed development is desirable.…”
Section: Species Interactionsmentioning
confidence: 99%